Increasing Knowledge Transfer to Employees Through Organizational Justice with Affective Commitment as Mediator - Pradana, Fawzi Rizki; Tjahjono, Heru Kurnianto; Nuryakin, Nuryakin (Jurnal Manajemen Bisnis, 2021)
Research aims: This study aims to determine the mediation of affective commitment on the effects of organizational justice, consisting of distributive justice, procedural justice, and interactional justice, on the knowledge transfer to employees at Diskominfo Kebumen Regency. The purpose of this research is also to find out the effect of distributive, procedural, and interactional justice on affective commitment, the effect of affective commitment on knowledge transfer, and the mediating role of affective commitment in the relationship between distributive, procedural, and interactional justice on knowledge transfer.Design/Methodology/Approach: This study used a quantitative approach with the path analysis method. Respondents in this study were employees at Diskominfo Kebumen. The sample used was 78 respondents who were taken by the total sampling technique.Research findings: This study found that distributive justice, procedural justice, and interactional justice significantly and directly affected affective commitment. The study results also showed a significant direct effect of affective commitment on knowledge transfer. Also, distributive justice, procedural justice, and interactional justice indirectly affected knowledge transfer through the mediation of affective commitment.Theoretical contribution: There are few previous studies on distributive, procedural, and interactional justice variables. The difference in this research lies in the research model development and the existing respondents’ characteristics.Practitioner/Policy implication: Based on this research, Diskominfo Kebumen, in the future, can pay attention to the variable aspects of this research in the decision-making process and the development of employee capabilities.Research limitation/Implication: The limitation in this study is that there are still few references related to variables, so mediation is needed. For example, no research addresses the direct relationship between knowledge transfer and organizational justice. Therefore, the scope for exploratory research is limited, and the research model and analysis methods must be adjusted.